Spent mushroom compost (SMC) – retrieved added value product closing loop in agricultural production - Jasińska, Agnieszka (Acta Agraria Debreceniensis, 2018)
Worldwide edible mushroom production on agro-industrial residues comprises of more than 11 million tons of fresh mushrooms per year. For 1 kg of mushrooms there is 5 kg of spent mushroom compost (SMC). This enormous amount of waste results in disposal problems. However, SMC is a waste product of the mushroom industry, which contains mycelium and high levels of remnant nutrients such as organic substances (N, P, K). The spent mushroom compost is usually intended for utilization, but there are increasing numbers of experiments focusing on its reuse in agricultural and horticultural production. Recently, the increase of the global environmental consciousness and stringent legislation have focused research towards the application of sustainable and circular processes. Innovative and environmentally friendly systems of utilisation of waste streams have increased interest of the scientific community. Circular economy implies that agricultural waste will be the source for retrieving high value-added compounds. The goal of the present work was to carry out a bibliographic review of the different scenarios, regarding the exploitation of this low cost feedstock with huge potential for valorisation.